Template attack of Crypto chip based on clustering - Zhen WU; Zhibo DU; Min WANG; Chunling XIANG (Tongxin xuebao)
The known-key establishment template and others full control of experimental equipment preconditions are required to implement the traditional template attack.The preconditions restrict the application scenario of template attack.The template attack is only applied to the device that the key input can be controlled.In order to resolve the restrictive preconditions,a novel method of template attack based on clustering was proposed.The clustering EM algorithm was modified according to the characteristics of information leakage model in the method.The modified clustering methods accurately fitted the leaked information probability model in the case of unknown key,the location of information leakage could be determined.Then the attack established the templates in the location,and implemented template matching.The proposed method eliminates the dependence of traditional template attacks on per-conditions and expand the application scenario of template attack.